Pengembangan Aplikasi Pencari Harga Terbaik Berbasis Selenium Web Crawler - Andriyani, Lina; Kristanto, Sepyan Purnama; Hakim, Lutfi; Suardinata, I Wayan (Software Development, Digital Business Intelligence, and Computer Engineering, 2023)
Online shopping or commonly known as an online shop or online shop is a place to purchase goods via the Internet. With so many e-commerce websites today, we can easily access information on goods from prices, specifications, and purchase transactions. However, e-commerce websites have now been built and used by many sellers, this sometimes makes it difficult for buyers to choose the items they are looking for. That way, it is certain that we do the manual method, namely visiting one by one e-commerce website to find out information on price comparisons about the item being sought. Therefore an application was created that aims to make it easier for users to compare the prices of fashion from three online stores, namely tokopedia, Bukalapak and Blanja.com. The method used is Extreme Programming (XP) and this application was built using the laravel PHP framework and using web crawling techniques.